The Neurobiology of Mutualistic Behavior: The Cleanerfish Swims into the Spotlight - Soares, Marta C. (Frontiers in Behavioral Neuroscience, 2017)
One of the most notorious examples of cooperation between different species happens in the cleaner-client fish mutualism. The best known cleaner fish species, the bluestreak Indo-Pacific cleaner wrasse Labroides dimidiatus has been a model system to study the evolution of cooperation between unrelated animals and between distinct species during the last couple of decades. Being a well-established model system for behavioural studies of cooperation offered an outstanding opportunity to identify the link between cooperation, social cognition, and to undertake proximate studies which were severely in need. This review surveys the current achievements of several recent studies, and the potential of the cleanerfish mutualism as relevant model system for future accomplishments in neuroendocrine research.